PENINGKATAN KETERAMPILAN BERBICARA ANAK MELALUI MEDIA GAMBAR SERI DI KELAS PAUD TAMAN POSYANDU AULIA BRABE - Ika Sulistiarini; A Zulkarnain Ali; Karunia Muda Setya Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to improve early childhood speaking skills through the use of picture series media at PAUD Taman Posyandu Aulia Brabe. Preliminary observations showed that several children experienced difficulties in expressing ideas verbally, lacked self-confidence, and had limited vocabulary. This study employed Classroom Action Research (CAR) using the Kemmis & McTaggart model in two cycles involving 10 children aged 4–5 years. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative and quantitative approaches. By implementing attractive and contextual picture series media, children are encouraged to organize story sequences, enhance vocabulary, and speak confidently in front of others. The research is expected to show significant improvements in four speaking indicators: confidence, fluency, coherence, and clarity of speech in early childhood.